Patrimonio cultural inmaterial y adquisición/desarrollo del lenguaje: tradición discursiva y psicodinámica oral - Asiain Ansorena, Alfredo; Aznárez Mauleón, Mónica (Huarte de San Juan. Filología y Didáctica de la Lengua, 2012)
This paper explores the didactic value of the Intangible Cultural Heritage (ICH) for child language acquisition and development. Starting from a definition of ICH that understands it as a constant interaction between the individual and the social, between the innate and the acquired, and with the embodied mind as its core, the paper analyzes the role that ICH plays in child education in general, and in child linguistic education in particular. More specifically, the paper highlights ICH as a discursive tradition that is offered to children by the socio-cultural environment, and as an oral psychodynamic that guides children’s learning in the interaction with adults.